Evaluation of the morphometric stability of the slot of metal orthodontic brackets using optical microscopy (Research, Society and Development, 2026)
The aim of this study was to evaluate the morphometric stability of the slots of metal orthodontic brackets from different commercial brands using optical microscopy. An in vitro experimental study was conducted in which 24 metal brackets for maxillary right central incisors with a 0.022” × 0.028” slot were evaluated, belonging to three commercial brands: American Orthodontics®, Morelli® Roth, and Azdent®. The slot dimensions in height, depth, and width were measured using high-precision optical microscopy. The data were subjected to descriptive and inferential statistical analysis, including the Shapiro–Wilk test, analysis of variance (ANOVA), and Tukey post hoc test, adopting a significance level of 5%. The results showed that all brands presented oversized slot dimensions compared with the nominal values declared by the manufacturers, with statistically significant differences among the groups for all evaluated dimensions (p < 0.05). it was concluded that the slots of the evaluated brackets did not present full dimensional conformity, revealing morphometric variations among the analyzed brands. optical microscopy proved to be an effective and reliable method for evaluating the morphometric stability of these devices, highlighting the need for stricter quality control in orthodontic bracket manufacturing processes.